Assessment of Oral Health-Related Quality of Life Among a Sample of Yemeni Population - Alqawsi, Mohammed Husien; Al-Shamahy, Hassan Abdulwahab (Open Access Pub, 2023)
The study aimed to assess the oral health condition and its impact on the quality of life (QoL) among a sample of Yemeni population. The study including 256 individuals who responded to the Oral Health Impacts Profile (OHIP) through completing a face-to-face survey of the OHIP-14 Arabic version. The data were collected by one dentist trained in the terms of oral health-related quality of life (OHRQoL). The study revealed that the impact of OHRQoL among the study sample was found with a weighted OHIP-14 score of 1.1 (0.9). Physical pain (3.72.3), followed by physical disability (2.42.2), and psychological disability (2.12.3) were the highest scoring. A significantly higher effect (p < 0.05) was found for the adults (18-44 years old) compared to those elderly individuals (> 64 years). The OHRQoL was better in male than in female and in employees than in both pensioners and un-employees. Females had a significantly higher effect when compared to males in the OHRQoL (p < 0.05). The unemployed subjects were significantly higher than those pensioners and employees in the OHRQoL (p < 0.05). The OHRQoL was also better in subjects with higher income and education than those participants with low. However, there were no significant differences for OHRQoL with respect to the educational level and monthly income of participants (p > 0.05). Conclusion, the quality of life is greatly affected by the oral health conditions of the elderly. This impact of oral health on quality of life has an association with individual and contextual variables.